2022
DOI: 10.18502/cmm.7.4.8406
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors, species distribution, and antifungal susceptibility of candidemia among hospitalized patients with COVID-19

Abstract: Background and Purpose: The pandemic of COVID-19 has caused a worldwide health crisis. Candidemia is a potentially lethal condition that has not yet been enough discussed in patients with COVID‐ 19. The current study aimed to investigate the prevalence of candidemia among Iranian COVID‐ 19 patients and characterize its causative agents and the antifungal susceptibility pattern. Materials and Methods: The present cross-sectional survey was carried out from March 2020 to March 2021 at Imam Khomeini Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Oral fungal carriage refers to the harmless presence of fungi, such as Candida species, as a part of the normal oral microbiome 6 . The oral mycobiome and fungal carriage in COVID-19 patients can differ from healthy individuals due to factors like invasive treatments, the virus’s impact on the immune system, and multidrug therapies 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral fungal carriage refers to the harmless presence of fungi, such as Candida species, as a part of the normal oral microbiome 6 . The oral mycobiome and fungal carriage in COVID-19 patients can differ from healthy individuals due to factors like invasive treatments, the virus’s impact on the immune system, and multidrug therapies 7 .…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19 infection, physiological changes in the oral cavity, stemming from factors like medication misuse, compromised immunity, vascular issues, inflammation, and poor oral hygiene during treatment, contribute to oral fungal colonization. This disruption can lead to oral fungal infections 7 , 11 . The virulence characteristics of these organisms, such as the release of esterase, proteinases, and haemolytic abilities that are necessary to colonize and invade human organs, might nevertheless create oral mycoses in COVID-19 patients in addition to host-related causes 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts and yeast-like fungi are single-celled opportunistic organisms that reproduce through budding. Generally, yeasts are incapable of causing disease in healthy human and animal hosts; for that, they require a substantial break in the host's defense system (1). Candida species are the most common yeasts that cause fungal infections, especially urinary tract infections, and can cause candiduria (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although Candida albicans is the most common cause of candiduria, non-albicans Candida species, particularly C. glabrata, and C. krusei, can be involved in the development of invasive candidiasis (1). Specific identification of Candida species helps choose the appropriate treatment because several non-albicans Candida species, such as C. krusei, are intrinsically resistant or less susceptible to several classes of antifungals, whereas others, including C. glabrata, develop acquired resistance following exposure to antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
“…Not only CAPA but also other fungal infections may complicate the course of COVID-19. Several recent studies reported an increasing incidence of candidaemia among COVID-19 patients [8][9][10][11][12]. Finally, other less common fungal infections, including pneumocystosis and mucormycosis, have been described in patients with severe COVID-19 [13][14][15].…”
mentioning
confidence: 99%